Mechanical response characteristics and key technology of construction control of roof of long span string beam structure - Ziguang Zhang; Cheng Zhang; Xiaopeng Li; Yida Guo; Shuai Kang; Ankang Hu (Scientific Reports)
Abstract The high-altitude assembly and tensioning construction of large-span beam string structures (BSS) offers numerous advantages, including structural simplicity, clear force transmission, minimal deformation, strong stability, structural adaptability, self-balancing capability, and ease of construction. However, it also presents technical challenges such as complex loading behavior, difficult deformation control, and high precision requirements during construction. This paper, based on the practical application in the Lingshui Gymnasium project in Hainan, employs a combination of theoretical analysis, numerical calculation, and in-situ testing to investigate the mechanical response characteristics of large-span BSS roofs. Under self-weight, the displacement of the support scaffolding causes the mid-span deflection on the left side of the beam-string to be greater than that on the right side. After the staged tensioning is completed, the mid-span of the beam-string exhibits an upward arching phenomenon. Under the standard combination of dead load and live load, the maximum deflection occurs at the mid-span of the beam-string, with a deflection-to-span ratio of 1/423, which meets the serviceability requirements. In terms of the improvement and innovation of construction technology, the supporting tire frame, tension cable, gusset, early warning and other aspects have been improved and innovated, and these improvements provide support for the improvement of the construction technology of the large-span tensioned string girder structure as well as the development and scientific and technological progress of the industry.